THE US POLICIES OF DEPORTATION OF ILLEGAL MEXICAN IMMIGRANTS IN THE EARLY XXI CENTURY: HUMAN CONSEQUENCES - T. V. Pantyukhina (Гуманитарные и юридические исследования)
The paper features the US deportation practices aimed to curb illegal Mexican immigration, which has not been a subject of research in Russian historiography. The Acts of 1986-2001 addressing illegal immigration empowered the executive branch in terms of arrest, detention and deportation. The main target of deportation policy is illegal immigrants of Mexican origin who make up the largest segment of unauthorized population in the USA. Millions of them are longterm US residents with mixed-citizenship families (a spouse and children with US citizenship). The paper highlights social, legal, and economic consequences for deportees’ families posed by deportations. These include family separation, substantial economic disadvantages for remaining family members, damaging impact on children’ mental and physical health. At the same time, some measures have been taken to protect undocumented immigrant youth, the most vulnerable segment of illegal immigrant population. The Deferred Action for Childhood Arrivals (DACA) program of 2012 provides temporary relief from deportation, Social Security numbers and two-year work authorization to immigrants who were brought to the USA as children. Another program – Development, Relief, and Education for Alien Minors (DREAM) Act – has been discussed in the Congress since 2001. It has been designed to provide undocumented young people who came to the USA as children with a pathway to US citizenship. Up to now, the bill has not become a law.